Abusive Constitutionalism in Peru: An analysis of presidential vacancy for moral incapacity and the events after November 9, 2020 - Rodríguez Mendoza, Massiel Jhadira (2021)
This article proposes a different view of the events that occurred on November 9, 2020, and later in Peru: the presidential vacancy of Martín Vizcarra because of the cause of moral incapacity and Manuel Merino’s assumption of the government. The view to analyzing the events is the hypothesis that Peru has rated Abusive Constitutionalism by the Congress of the Republic, a hypothesis that is sought to prove throughout the article. First, the research details and explains the initial conceptions of Abusive Constitutionalism and how the doctrine has been delimiting the concept. Second, new forms of manifestation are proposed that abusive Constitutionalism may have beyond its initial definition so that it can include other situations in which democracy is being undermined through seemingly constitutional mechanisms. Third, a critical study is carried out on the Peruvian system and the constitutional institutions it has adopted in its organization, which allows identifying the weaknesses of its political structure and how Abusive Constitutionalism can manifest itself. Fourthly, the figure of the vacancy for moral incapacity is analyzed and what its possible delimitations might be. Finally, the final analysis is carried out to the events that occurred on November 9, 2020, and the presence of Abusive Constitutionalism in the decision of the Congress.